The postcolonial studies reader - Ashcroft, Bill, 1946-; Griffiths, Gareth, 1943-; Tiffin, Helen (Abingdon, Oxon ; New York, USA : Routledge, 2025)
"The most comprehensive collection of postcolonial writing theory and criticism, this third edition has been thoroughly revised and updated to include 124 from key works in the field. Leading, as well as lesser-known figures in the fields of writing, theory and criticism contribute to this inspiring body of work that includes sections on nationalism, hybridity, diaspora and globalization. As in the first two editions, this new edition of The Postcolonial Studies Reader ranges as widely as possible to reflect the remarkable diversity of work in the discipline and the vibrancy of anti-imperialist and decolonizing writing both within and without the metropolitan centres. This volume includes new work in the field over the decade and a half since the second edition was published. Covering more debates, topics and critics than any comparable book in its field The Postcolonial Studies Reader provides the ideal starting point for students and issues a potent challenge to the ways in which we think and write about literature and culture"--
Includes bibliographical references and index.
Keywords: Commonwealth literature (English) -- History and criticism; English literature -- Developing countries -- History and criticism; Postcolonialism -- Commonwealth countries; Postcolonialism in literature; Decolonization in literature; Imperialism in literature; Colonies in literature; Literary criticism; Essays